SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL STUDIES OF SOME METAL (II) COMPLEXES OF TRIDENTATE LIGAND DERIVED FROM ETHYLENEDIAMINE, NITROBENZALDEHYDE AND AMINOBENZOPHENONE - Ajibulu, K E; Okoronkwo, A E; Owolabi, J B; Oyetayo, V O (Journal of Chemistry, 2022)
The Schiff base ligand and its metal complexes derived from ethylenediamine, nitrobenzaldehyde and aminbenzophenone were prepared using hydrated metal salts of Ni(II), Co(II) and Mn(II) and characterized by molar conductivity, magnetic susceptibility measurement elemental analysis, FTIR, GC-MS, UV-Vis spectroscopy and (1H, 13C) NMR spectra. Some physical parameters were obtained using molar conductance measurement and melting point determination. From the analytical and spectroscopic data, N donor atoms of the Schiff base ligand and N of NH2 group participated in coordination with metal (II) ions proposed to be a tridentate ligand and octahedral geometry was proposed for the complexes of Co, Ni while tetrahedral geometry proposed for Mn respectively. The antimicrobial activity of the ligand and its metal complexes were compared with the standard drugs Amoxicillin and Nystatin by screening them against isolates of two Gram-positive, three Gram-negative and two fungal strain, using agar well diffusion method for bacteria while the fungal cultures were maintained on Sabouraud liquid medium. The results obtained showed that the metal complexes were more potent against Gram-positive bacterial and fungi than the free ligand, while the ligand showed greater activity against Gram-negative bacterial than the metal complexes.